U.S.-UK Voting Cohesion in the United Nations General Assembly: Important Votes (2001–2019) - A. O. Mamedova (Vestnik MGIMO-Universiteta)
The article analyzes US-UK voting cohesion in the United Nations General Assembly in 2001 – 2019 based on the annual lists of important votes drawn up by the US Department of State. Voting cohesion in the UNGA demonstrates the level of support for US policies in this representative international forum. Since most UNGA resolutions are not binding, countries have more room for maneuver compared to voting in the UN Security Council. Washington pays close attention to other countries’ voting behavior in the UNGA, especially when it comes to Israel-related issues. Whereas the Anglo-American Special Relationship has been extensively studied with the focus on the military and political aspects, US-UK interaction in international organizations, especially in the UN, deserves greater attention. Both countries use their permanent membership of the Security Council to promote their interests. Nevertheless, US-UK voting cohesion in the UNGA has not attracted much attention yet, although it can help to objectively assess the interaction of these powers in the world arena. Four groups of important resolutions were identified for comparison: human rights, Israeli-Palestinian conflict, nuclear non-proliferation and international security, as well as sanctions and development. In 2001 – 2019 U.S.-UK voting cohesion on important resolutions was relatively high. Nevertheless, under Republicans George W. Bush and Donald Trump it was lower than during Barack Obama’s presidency. Despite the special relationship, the UK often aligns itself with the EU countries when voting in the UNGA. We paid special attention to resolutions on which the countries diverged, although Washington did not vote in complete isolation. U.S.-UK cohesion was higher on non-proliferation and human rights. At the same time, there were differences regarding the Israeli-Palestinian conflict and development, especially in those cases when the US and the EU disagreed. Divergences were apparent when the US was prone to act unilaterally.